2014
DOI: 10.1007/s10103-014-1680-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser (λ 660 nm) and LED (λ 630 nm) photobiomodulation on formocresol-induced oral ulcers: a clinical and histological study on rodents

Abstract: The aim of this study was to evaluate, clinically and histologically, the influence of laser and LED photobiomodulation in the healing of formocresol-induced oral mucosa ulcers of rats. We used 60 Wistar rats in which oral ulcers were induced on the gingiva of the lower incisors. Forty-eight hours after inducing the ulcers, the animals were divided into three groups: laser, LED, and untreated. Animals from the laser group received irradiation with GaAlAs, 660 nm, CW, 40 mW, φ 4 mm(2), 4.8 J/cm(2). Animals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
1
9
0
4
Order By: Relevance
“…Several studies have been reported that 630 nm and 640 nm LED irradia-tion with 4-24 J/cm 2 decreased wound surface area. 10,[15][16][17] Our results agree with the findings from several other studies that used 640 nm and 700 nm LED with 15-16 J/cm 2 to stimulate fibroblast proliferation and collagen production on excision wound in rats. 16,18,19 In the present study, epithelial gap of LED group showed signifi-…”
Section: Pcna Immunoreactive Fibroblastsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have been reported that 630 nm and 640 nm LED irradia-tion with 4-24 J/cm 2 decreased wound surface area. 10,[15][16][17] Our results agree with the findings from several other studies that used 640 nm and 700 nm LED with 15-16 J/cm 2 to stimulate fibroblast proliferation and collagen production on excision wound in rats. 16,18,19 In the present study, epithelial gap of LED group showed signifi-…”
Section: Pcna Immunoreactive Fibroblastsupporting
confidence: 91%
“…healing of excision wound in the rat. The parameters of LED irradiation used in this study are based on previous studies 7,10,11. LED irradiation was increased the wound closure rate and colla-gen density in situ at day 7 post excision wound, This result suggest that LED irradiation stimulate the fibroblast proliferation and collagen deposition in the granulation tissue.…”
mentioning
confidence: 83%
“… Larkin-Kaiser et al [ 89 ] No info Source, laser; wavelength, 800 and 970 nm; power, 3 W; frequency, –; beam area, – Irradiance, –; time, 4 min; energy, 360 J; radiant exposure, – Applied to skeletal muscle before resistance exercise, NIR light therapy effectively attenuated strength loss. de Carvalho et al [ 90 ] No info Source, GaAlAs (660 nm, laser) and InGaAlP (630 nm, LED); wavelength, 660 and 630 nm; power, 40 mW (laser) and 150 mW (LED); frequency, CW; beam area, 4 mm 2 (laser) and 0.8 cm (LED) spot Irradiance, –; time, –; energy, –; radiant exposure, 4.8 J/cm 2 Laser and LED photobiomodulation were effective in accelerating the healing of formocresol-induced oral ulcers in both clinical and histological aspects. Ban Frangez et al [ 92 ] No info Source, LED; wavelength, 470, 625, 660 and 850 nm; power, –; frequency, kHz range; beam area, – Irradiance, 2.16–8.23 mW/cm 2 ; time, 3 min; energy, –; radiant exposure, – Photobiomodulation using LED improved the sperm motility in asthenozoospermia regardless of wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Rats were anaesthetized with an intramuscular injection of ketamine hydrochloride 10% and xylazine hydrochloride 2% (AMOUN, Egypt) at a dosage of 0.06 ml/100 g and 0.03 ml/100 g, respectively. A homogeneous standardized circular oral cheek ulcer was obtained using 5mm biopsy punch (13), followed by perpendicular application of a flexible swab with a cotton tip soaked in formocresol for 60s (14).…”
Section: Methodsmentioning
confidence: 99%